Integrative Analysis of Metabolomics and Transcriptomics Data Identifies Prognostic Biomarkers Associated With Oral Squamous Cell Carcinoma - Zuo, Lihua; Chen, Zhuo; Chen, Lihuang; Kang, Jian; Shi, Yingying; Liu, Liwei; Zhang, Shuhua; Jia, Qingquan; Huang, Yi; Sun, Zhi (Frontiers in Oncology, 2021)
Background: Oral squamous cell carcinoma (OSCC) is the most malignant neoplasm in oral cancer. There is growing evidence that its progression involves altered metabolism. The current method of evaluating prognosis is very limited and metabolomics may provide a new approach for quantitative evaluation. The aim of the study is to evaluate the use of metabolomics as prognostic markers for patients with OSCC. Methods: A analytical platform, ultra high performance liquid chromatography-quadrupole/orbitrap high resolution mass spectrometry (UHPLC-Q-Orbitrap HRMS), was used to acquire the serum fingerprinting profiles from a total of 103 patients of OSCC before and after the operation. The total of 103 OSCC patients were assigned to either a training set (n=73) or a test set (n=30). The potential biomarkers and the changes of serum metabolites were profiled and correlated with the clinicopathological parameters and survival of the patients by statistical analysis. To further verify our results, we linked them to gene expression using data from the and Kyoto Encyclopedia of Genes and Genomes (KEGG). Results: In total, 14 differential metabolites and 5 disturbed pathways were identified between preoperative group and postoperative group. Succinic acid change-low, hypoxanthine change-high tumours, tumour grade, tumour stage indicated a trend towards improved recurrence-free survival (RFS). What whether in training set or a test set. In addition, succinic acid change-low, hypoxanthine change-high and tumour grade provided the highest predictive accuracy of the patients with OSCC. KEGG enrichment analysis showed that the imbalance of amino acid and purine metabolic pathway may affect the prognosis of oral squamous cell carcinoma. Conclusions: The changes of metabolites before and after operation may be related to the prognosis of OSCC patients. UHPLC-Q-Orbitrap HRMS serum metabolomics analysis could be used to further stratify the prognosis of patients with OSCC. These results can better understand the mechanisms related to early recurrence and help develop more effective therapeutic targets.